SCM440 주조재와 F-05-140 소결재의 이종재료 마찰용접 및 공정 조건에 따른 접합 특성 연구 - 이지성; 이한성; 송은효; 안병민 (한국분말재료학회지, 2024)
Friction welding, which uses heat and plastic flow to join metals, is expanding across industries due to its ability to weld heterogeneous alloys and simple process. However, process research is essential for materials with complex geometries, and limited research has been conducted on friction welding between cast and sintered metals. This study analyzed the mechanical properties and microstructural evolution of the joint by controlling the rotational speed and friction pressure, which affect the removal of the heat-affected zone in friction welding of casted SCM440 and sintered F-05-140. Hardness mapping and microstructure observations with material transition were performed to investigate the correlation between phase behavior and welding conditions. These results are anticipated to reduce costs and improve the mechanical properties of key mobility components.
Keywords: Friction welding; Dissimilar metals; Heterogeneous joint; Heat-affected zone; Thermo-mechanically affected zone